The Anglican Church in Malaysia Evolving Concepts, Challenging Contexts, Emerging Subtexts - Jarvis, Edward (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines the Anglican Church in Malaysia from multiple angles, unpacking its history from British colonialism to today's Muslim-majority Asian nation. Analyzing tense Christian-Muslim dialogue and volatile intercommunity relations, themes of ethnicity, identity, gender, and multiculturalism intersect in contexts of war, insurgency, and national independence. The Church's two centuries of history unfold chronologically, but this study goes far beyond mere description of events; it is a critical, multidisciplinary, multilayered discussion that integrates contemporary, archival, and scholarly perspectives. It focuses on high-pressure interfaces between colonialists, clergy, sultans, indigenous, and immigrant groups. The roles of education and healthcare-as evangelism, or perhaps incentivization-are investigated, within evolving models of mission, conversion, and the broader context of Anglicanism in crisis. These diverse threads intertwine to produce a concise but comprehensive three-dimensional portrait of the Anglican Church in Malaysia.
1. Introduction -- 2. "To carry the Church with us wherever we go"-The Arrival of Church and Empire in Southeast Asia and Malaysia -- 3. "In the lands of Heathenism"-Conquests and Contradictions in Colonial Malaysian Mission -- 4. "Give me eight more young and devoted priests"-Setbacks and Successes in the Early Twentieth Century -- 5. "Rejoicing in tribulation, full of hope"-The Church and the Second World War -- 6. "A fertile field for evangelism"-The Postwar Church, the Malayan Emergency, and Missionary Evolution -- 7. "The Christian voice in a Muslim majority context"-The Challenges and Dilemmas of Today's Church in Malaysia -- 8. "From the shores of the Peninsula or from the deck of the ship"-Theological and Missiological Perspectives and Viewpoints -- 9. Afterword.
Keywords: Theology; Christianity and the social sciences; Christian sociology; Southeast Asia-History.; Christian Theology; Social Scientific Studies of Christianity; History of Southeast Asia